Osteoporosis and risk of fracture in heart transplant patients - Forien, Marine; Coralli, Romain; Verdonk, Constance; Ottaviani, Sébastien; Ebstein, Esther; Demaria, Lucie; Palazzo, Elisabeth; Dorent, Richard; Dieudé, Philippe (Frontiers in Endocrinology, 2023)
Significant bone loss occurs after heart transplantation, predominantly in the first year, with increased risk of incident fractures. The goal of this study was to evaluate the prevalence of fragility fractures in a population of heart transplantation patients and to identify the independent risk factors for fractures. This was a prospective monocentric study that included patients with heart transplantation occurring < 10 years who were undergoing heart transplantation monitoring. All patients underwent bone mineral density evaluation by dualenergy X-ray absorptiometry and radiographies to establish the presence of vertebral fractures. We included 79 patients (61 men); the mean age was 56.8±10.8 years. The mean time between transplantation and inclusion was 32.3±35.0 months. Incident fractures were diagnosed in 21 (27%) patients after heart transplantation. Vertebral fractures were the most frequent (30 vertebral fractures for 15 patients). Osteoporosis was confirmed in 22 (28%) patients. Mean bone mineral density at the femoral neck and total hip was lower with than without fracture (femoral neck: 0.777±0.125 vs 0.892±0.174 g/cm 2 , p<0.01; total hip: 0.892±0.165 vs 0.748±0.07 g/cm 2 , p<0.001), with a significant result on multivariate analysis.The mean time from transplantation to the first fracture was 8.0±7.6 months. Our study confirmed a high vertebral fracture risk in heart transplant patients, especially during the first year after transplantation